EFEKTIVITAS APLIKASI BEBERAPA HERBISIDA SISTEMIK TERHADAP GULMA PADA PERKEBUNAN KELAPA SAWIT RAKYAT - Yardha .; Araz Meilin (Jurnal Agroekoteknologi, 2010)
ABSTRACTThe objective of the study were to find the dominant weeds in palm oil plantation before application of weeds control using effective active compound of systematical herbicide. Research done in Glorious Countryside Petaling, public plantation, River Gelam, Muaro Jambi, Jambi Province in January--Februari 2008. The research used active compound of herbicide gliphosate amineisoprophyll, 2,4 D-dimethyllamine, gliphosate isoprophyllamine + 2,4 D dimethyllamine, and triasulphuron 75%. The study was conducted using Randomized Completely Design, with 5 replicates. Data were analyzed by Duncan’s Multiple Range Test (DMRT). Data analysis of weeds vegetationusing SDR values. Result found 5 dominants weed species before herbicide application were Imperata cylindrica (with SDR value 27,8%), followed with Asystasia intrusa ( SDR = 9,4%), Affinae melastoma ( SDR = 9,2%), Repens panicum ( SDR = 8,2%), and Borreria alata ( SDR = 7,7)). Glyphosate isoprophyllamine of herbicide active compound which suitable to control grass weed species; while 2,4 D dimethyllamine active compound more suitable to control the wide leaf weed. Imperata cylindrica controlled with herbicide using gliphosate isoprophyllamine active compounds. Asystasia intrusa and Affinae melastoma controlled with 2,4 D dimethyllamines active coumpound. Weed competition reduce of crop production.Key words: active compound, herbicide, weed, palm oil